KEPEMIMPINAN VISIONER DALAM PENINGKATAN MUTU SEKOLAH - Hermawan, Hermawan (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
This article aims to investigate the influence of Visionary Leadership on School Quality. The research methodology involved conducting a literature review, specifically searching for relevant data sources on Google Scholar that discuss how Visionary Leadership affects school quality. The findings of the literature review indicate that Visionary Leadership plays a pivotal role for modern-day school leaders. The traits associated with visionary leadership demonstrate a leader's capacity to drive change and possess a clear vision of the organization's trajectory. In this regard, visionary leadership is recognized as a source of motivation for facilitating change and enhancing school quality. This suggests that leaders exhibiting visionary leadership styles not only impact the educational process within schools but also contribute significantly to the overall improvement of education quality.